2017
DOI: 10.1155/2017/8648137
|View full text |Cite
|
Sign up to set email alerts
|

Development and Validation of a Decision-Making Stratification Algorithm to Optimize the Use of Rapid Diagnostic Testing for Patients with Staphylococcus Bacteremia

Abstract: Purpose To evaluate whether introducing rapid diagnostic testing in conjunction with implementing a stratification algorithm for testing eligibility would be an appropriate clinical and cost saving approach. Method An internal concurrent 4-month observational study was performed. Positive blood cultures continued to be worked up in accordance with standard of care. An additional call to the infectious disease (ID) pharmacy service occurred for all positive blood cultures with Gram-positive cocci in clusters (G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…This could explain the emergence of antimicrobial resistance observed in hospitals and supports the desperate need to establish antimicrobial stewardship programs and recruit infectious disease clinical pharmacists. 35 , 36 Omeprazole was the most individual drug associated with PEs, despite its safety profile and controversy over excessive prescription by physicians. Reports have shown that the rate of inappropriate prescribing of proton pump inhibitors for stress ulcer prophylaxis could reach up to 71%, which has been attributed to prescribing physician ignorance of proper indications and its side effects such as Clostridium difficile infections.…”
Section: Discussionmentioning
confidence: 99%
“…This could explain the emergence of antimicrobial resistance observed in hospitals and supports the desperate need to establish antimicrobial stewardship programs and recruit infectious disease clinical pharmacists. 35 , 36 Omeprazole was the most individual drug associated with PEs, despite its safety profile and controversy over excessive prescription by physicians. Reports have shown that the rate of inappropriate prescribing of proton pump inhibitors for stress ulcer prophylaxis could reach up to 71%, which has been attributed to prescribing physician ignorance of proper indications and its side effects such as Clostridium difficile infections.…”
Section: Discussionmentioning
confidence: 99%
“…A recent review has shown that the use of rapid diagnostic tests such as the PNA-FISH is a cost-effective strategy that was associated with high therapeutic effectiveness and health care cost savings [40]. In addition, it has been demonstrated that direct identification of organism in positive blood cultures bottles using MALDI-TOF MS or QuickFISH V R may have a clinical impact in patients with bacteraemia and improve appropriateness of antibiotic therapy [10,[41][42][43].…”
Section: Discussionmentioning
confidence: 99%
“…It is estimated that AMR would cause 10 million deaths by 2050 5 . The AMR crisis has necessitated global efforts to implement containment measures to reduce antibiotic consumption and utilise current resources wisely and efficiently 6‐10 …”
Section: Introductionmentioning
confidence: 99%
“…5 The AMR crisis has necessitated global efforts to implement containment measures to reduce antibiotic consumption and utilise current resources wisely and efficiently. [6][7][8][9][10] The analyses of pharmaceutical sales data from 71 countries revealed an increase by 36% in antimicrobial consumption between…”
mentioning
confidence: 99%